Effectiveness of Milieu Therapy in reducing conflicts and containment rates among schizophrenia patients - Bhat, Sandhya; Rentala, Sreevani; Bevinahalli Nanjegowda, Raveesh; Belsiyal Chellappan, Xavier (Investigación y Educación en Enfermería, 2020)
Objective. To evaluate effectiveness of Milieu Therapy in reduction of conflict and containment rates among schizophrenia patients. Methods. This study utilized quasi experimental non-equivalent control group pre-post design. One hundred schizophrenia patients admitted in acute psychiatric wards were non-randomly assigned to either of the experimental (n=50) or control group (n=50). The experimental group received both milieu therapy and routine hospital treatment. The Milieu Therapy intervention Included environmental modification and structuring ward activities, establishing effective interaction with patient, and teaching caregivers on managing conflict behavior of patient. The control group received only routine treatment in the hospital. Outcome measures on conflict and containment rates were evaluated for both the groups at baseline and at 2nd, 3rd and 15th day. The Patient–Staff Conflict Checklist Shift Report (PCC-SR) was used to collect information about rates of conflict and containment. Results. Compared with control group, the experimental group participants showed decrease in aggressive behavior, self-harm behavior and general rule breaking behavior at baseline and 2nd, 3rd and 15th day (F=4.61, p<0.004, η2=0.04; F=11.92, p<0.001, η2=0.11; F=6.94, p<0.001, η2=0.06) over seven days interval. Conclusion. The present study findings provided evidence for the effectiveness of integrating Milieu Therapy in psychiatric acute wards in reducing conflict behaviors among schizophrenia patients. Milieu therapy should be considered as an integral part of psychiatric care settings in these patients. How to cite this article: Bhat S, Rentala S, BN Raveesh, Chellappan XB. Effectiveness of Milieu Therapy in reducing conflicts and containment rates among schizophrenia patients. Invest. Educ. Enferm. 2020; 38(1):e06.